The Frequency, Nature, and Effects of Coerced Debt Among a National Sample of Women Seeking Help for Intimate Partner Violence. (September 2020) - Adams, Adrienne E.; Littwin, Angela K.; Javorka, McKenzie
This study examines the frequency, nature, and effects of coerced debt, defined as non-consensual, credit-related transactions that occur in intimate relationships where one partner uses coercive control to dominate the other. The sample includes 1, 823 women who called the National Domestic Violence Hotline. Results suggest that coerced debt, from both coercive and fraudulent transactions, is a common problem and is significantly related to control over financial information, credit damage, and financial dependence on the abuser. This study supports the need for policy reform and victim services aimed at addressing coerced debt, thereby mitigating a potentially significant economic barrier to safety.